Nepal in BIMSTEC: Contribution, Achievements and Future Directions - Sharma, Pratima (Journal of Political Science, 2025)
This paper investigates Nepal's participation in the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC), a key regional organization. Nepal promotes regionalism by adhering to the principles established by the United Nations and actively working to address regional challenges while enhancing opportunities through cooperative initiatives. Since joining BIMSTEC in 2004, Nepal has engaged extensively in the BIMSTEC framework. This study employs qualitative descriptive and analytical methods to examine Nepal's perspective on BIMSTEC and its role in fostering regional cooperation, particularly through the lens of liberal inter-governmentalism. The information is collected from various secondary sources. A thorough analysis of these resources shows that Nepal strongly supports the BIMSTEC initiative, which is clear in its discussions on foreign policy. Nepal views BIMSTEC not as a substitute for other regional bodies, but to enhance cooperation across different sectors within the region. The successful execution of BIMSTEC agreements and collaborative initiatives is a key measure of the likelihood of attaining substantial results within the BIMSTEC region.